Turn On and Tune In: Problematizing the Relationship between Soundscape and Tourist Mood - Eşref Ay; Semra Günay (Journal of Tourism, Sustainability and Well-being, 2023)
This article aims to determine the effect of soundscape on tourist mood within the framework of sound pressure and sound types to provide a more effective destination experience. A theme park and a recreational area located in a central business district, which are important urban tourism attractions, were taken as research areas. For data collection, a Positive and Negative Affect Schedule was used. Furthermore, sound pressure measurements and environmental sound recordings were carried out through sound walks. At these locations, sound pressure levels and the types of sounds that make up the soundscape were identified. It was found that nature sounds, society, and human-induced sounds were predominantly heard in study areas. The results revealed that the sound types in soundscape, which have unique sound types in both study areas, produce a positive affect on tourists even if their pressure increases.